Using papain enzyme to improve feed protein utilization for kissing gourami (Helostoma temminckii) - Yulisman, Yulisman; Amin, Mohamad; Mukti, Retno Cahya; Astara, Nurcheni (Acta Aquatica: Aquatic Sciences Journal, 2022)
The aim of this research was to determine of optimum dosage of papain enzyme in feed for kissing gourami. This research used Completely Randomized Design non-factorial, consist of four treatments and three replications, namely: P0 (wihout papain supplementation in feed/as a control), P1 (1.5% papain in feed), P2 (3.0% papain in feed), and P3 (4.5% papain in feed). Kissing gourami with initial body weight of 0.51+0.07 g were stocked in each aquarium (volume 20 L of water) of 2 fish per litre of water. Fish reared for 45 days. During rearing time, fish were fed three times a day at satiation. Observed variable were growth, feed efficiency, protein retention, survival rate, and water quality of rearing media of kissing gourami. The growth, feed efficinecy, protein retention, and survival of kissing gourami were analyzed by analysis of variance. If the data significant different were analyzed by Least Significant Different test. Water quality of rearing media were descriptive analysis. The result showed that addition of 1.5% papain enzyme in feed result in the growth, feed efficiency, protein retention, and survival of kissing gourami were highest. The weight growth of fish of 0.44 g per fish, feed efficiency of 38.66%, protein retention of 23.60%, and survival of 97.78%. Water quality of rearing media were still in tolerance range for kissing gourami.Keywords: Feed efficiency; Growth; Kissing gourami; Papain enzyme; Protein retention